Multiple Input Multiple Output Slot Antenna Design With -22 Db Isolation Without Decoupling Structure For Application On Ultra Wide Band - Nadilla Marselina; Uzma Septima; Amelia Yolanda; Yustini Yustini (Politeknik Negeri Padang, 2024)
Technology that is always evolving requires us to always make the latest innovations, one of which is in the field of telecommunications. Currently, multiple input multiple output (MIMO) technology is widely used in ultra wideband (UWB) systems to overcome the effects of multipath fading. Multiple antennas are used to increase channel capacity. Two-element MIMO UWB systems have several techniques for obtaining good isolation between antenna elements. In this final project, the design and analysis of the change of a single UWB slot antenna into a 2-element MIMO UWB antenna is carried out by placing the antenna elements asymmetrically to get high antenna isolation. The proposed UWB MIMO antenna has a very compact size of 42×25 mm2. The fed slot microstrip antenna acts as a single UWB antenna element. Antenna design using CST Study Suite software. In the simulation results, a single UWB slot antenna that is modified into a UWB MIMO antenna has a return loss of -28 dB, a bandwidth of 7.2514 GHz, isolation below -20 dB, a VSWR of VSWR 2 in the frequency range of 3.7002 GHz to 9.6546 GHz, the gain reaches 3.2 dBi, and radiation pattern which is quasi omnidirectional.